Natural medicinal resources and their therapeutic applications - Joanna Ziemska; Tomasz Szynal; Małgorzata Mazańska; Jolanta Solecka (National Institute of Public Health - National Institute of Hygiene, 2019)
Natural medicinal resources are a country's natural wealth. Natural medicinal waters, medicinal gases, and peloids have many properties that enable their use in the treatment of gastrointestinal, circulatory, respiratory, bone and joint, and skin and soft tissue disorders. Balneotherapy can be also applicable in prevention of many diseases and rehabilitation. At present, because there are several chemicals of synthetic origin, there is a need to search for nonpharmacological approaches and explore natural healing sources, which better fit the human body. Compared to synthetic drugs, these resources rarely show side effects, which increases the comfort of therapy. The use of natural medicinal resources in the form of treatments in health resort medicine centers under the supervision of balneologists, combined with the healing properties of the climate, contributes not only to the reduction of treatment time for many diseases but also to improvement of therapy's results. The article discusses natural medicinal resources and some of their therapeutic applications.